2018
DOI: 10.1103/physrevfluids.3.053901
|View full text |Cite
|
Sign up to set email alerts
|

Absolute/convective secondary instabilities and the role of confinement in free shear layers

Abstract: We study the linear spatiotemporal stability of an infinite row of equal point-vortices under symmetric confinement between parallel walls. These rows of vortices serve to model the secondary instability leading to the merging of consecutive (Kelvin-Helmholtz) vortices in free shear layers, allowing us to study how confinement limits the growth of shear layers through vortex pairings. Using a geometric construction akin to a Legendre transform on the dispersion relation, we compute the growth rate of the insta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…Alternatively, it has been demonstrated that a numerical approach based on the post-processing of the numerical linear impulse response can well describe the long-time behaviour of the impulse response (Brancher & Chomaz 1997; Delbende & Chomaz 1998; Delbende, Chomaz & Huerre 1998; Gallaire & Chomaz 2003; Mowlavi, Arratia & Gallaire 2016; Lerisson 2017; Arratia, Mowlavi & Gallaire 2018). The procedure consists of a demodulation of the signal along one direction using the Hilbert transform, which leads to the complex analytic continuation of the real response, the analytic signal.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has been demonstrated that a numerical approach based on the post-processing of the numerical linear impulse response can well describe the long-time behaviour of the impulse response (Brancher & Chomaz 1997; Delbende & Chomaz 1998; Delbende, Chomaz & Huerre 1998; Gallaire & Chomaz 2003; Mowlavi, Arratia & Gallaire 2016; Lerisson 2017; Arratia, Mowlavi & Gallaire 2018). The procedure consists of a demodulation of the signal along one direction using the Hilbert transform, which leads to the complex analytic continuation of the real response, the analytic signal.…”
Section: Introductionmentioning
confidence: 99%